Micro-electromembrane extraction across free liquid membranes. Instrumentation and basic principles - Kubáň, Pavel; Boček, Petr (Journal of chromatography. A, 2014)
A micro-electromembrane extraction (μ-EME) technique using electrically induced transfer of charged analytes across free liquid membranes (FLMs) was presented. A disposable extraction unit was proposed and it was made of a short segment of transparent perfluoroalkoxy tubing, which was successively filled with three liquid plugs serving as acceptor solution, FLM and donor solution. These plugs formed a three-phase extraction system, which was precisely defined, that was stable and required μL to sub-μL volumes of all respective solutions. Basic instrumental set-up and extraction principles of μ-EME were examined using an anionic and a cationic dye, 4,5-dihydroxy-3-(p-sulfophenylazo)-2,7-naphthalene disulfonic acid trisodium salt (SPADNS) and crystal violet, respectively. Transfers of the charged dyes from donor into acceptor solutions across FLMs consisting of 1-pentanol were visualized by a microscope camera and quantitative measurements were performed by UV-vis spectrophotometry. The effects of operational parameters of μ-EME system were comprehensively investigated and experimental measurements were accompanied with theoretical calculations. Extraction recoveries above 60% were achieved for 5min μ-EME of 1mM SPADNS at 100V with repeatability values below 5%. Selectivity of FLMs was additionally examined by capillary electrophoretic analyses of acceptor solutions and the potential of FLMs for μ-EME pretreatment of samples with artificial complex matrices was demonstrated.
Keywords: Reproducibility of Results; Cations; reprodukovatelnost výsledků; Free liquid membranes; kationty; elektroforéza kapilární; Micro-electromembrane extraction; pentanoly; spektrální analýza; Anions; anionty; membrány umělé; barvicí látky; Membranes, Artificial; Spectrum Analysis; SPADNS, UV–vis spectrophotometry; Electrophoresis, Capillary; Coloring Agents; Pentanols